Efeitos comportamentais em juvenis de Tambaqui (Colossoma macropomum, CUVIER, 1818) submetidos ao pesticida clorpirifós - VIANA, Daniela Andressa Ferreira (Universidade Federal do Oeste do Pará, 2024)
The use of pesticides has become a frequent problem in Brazil and in the world due to the damage it causes to the environment and public health. Pesticides classified as organophosphates are considered highly toxic due to their mechanism of action, as they inhibit the enzyme acetylcholinesterase, causing the accumulation of acetylcholine in the synaptic clefts, which generates symptoms of the cholinergic syndrome. Among the organophosphates, chlorpyrifos is a pesticide widely used in the national territory as an alternative to combat pests in agriculture. Thus, the present study characterized the behavioral alterations of the fish Colossoma macropomum (tambaqui) in an Acute Toxicity Test (96 h) with the pesticide chlorpyrifos and evaluated the manifestations of the symptoms of the cholinergic syndrome derived from the Central Nervous System (CNS) and Peripheral Nervous System (PNS). The methodology used was the Acute Toxicity Test for fish, formulated by the Organization for Economic Cooperation and Development (OECD), the protocol was adapted for the animal model used, juvenile tambaqui. These animals have an average weight of 1.02 ± 0.06 g and were distributed in groups of n= 15, formed by triplicates of 5 individuals per aquarium, for each concentration of the established lethality range: 2.5; 10; 15; 25 and 45 μg/L, plus a control (blank). After analyzing the data, a mortality rate of 16.25 % was obtained and, from the observed behavioral changes, it was possible to establish a grouping, resulting in 10 (events or score) of behaviors manifested by the animals during the period of the experiment. The results were obtained in 48 hours, when the animals presented the proposed alterations, evidenced by previous studies. Then, the behavioral association with the behavioral symptoms of the cholinergic syndrome was performed, making it possible to observe two types of manifestations of neurological alterations.